Numerical study of a three-dimensional forced laminar flow in a channel equipped with a perforated baffle - Benzenine, Hamidou; Saim, Rachid; Abboudi, Said; Imine, Omar; Öztop, Hakan Fehmi; Abu-Hamdeh, Nidal (Taylor & Francis Inc, 2018)
The present work concerns a numerical study of a three-dimensional laminar flow in forced convection crossing a rectangular channel provided with a baffle attached on its lower wall. The conservation equations for mass, momentum, and energy are solved by the finite volume method based on the SIMPLE algorithm for pressure-velocity coupling scheme. The effect of the insertion of a perforated baffle at different perforation volumes was analyzed. The results presented show the temperature and velocity contours obtained for two different planes (XY and XZ) passing through the center of the baffle. The average friction coefficient, the average Nusselt number and the heat flux are presented for different perforation volumes of the baffle and for different Reynolds numbers. The study shows that although the solid baffle improves heat transfer, the use of a perforated baffle attached to the same position, further enhances heat transfer (from 0.03% to 14.52%), which provides, economically, a very good material reduction (from 5.18% to 82.96%) and mechanically, less flow resistance and therefore better performance.
Keywords: Heat-Transfer Enhancement; Roughened Rectangular Channel; Turbulent-Flow; Fluid-Flow; Circular Tube; Geometry Parameters; Square Channel; Performance; Convection; Exchanger